La The city and the architecture of fear. A comparative conceptual study between the contemporary luxurious gated community and the medieval bastide (2014)
The following article intends to display a series of conceptual approaches aimed to study the interactions between fear, architecture and the city, focusing on the functional and formal analysis of its defensive elements and the relationship with its immediate open environment. The case study takes place in the Metropolitan Area of Guadalajara and its luxurygated communities, in contrast with an analog situation experienced in the medieval city and its fortified elements. The premise supposes that the rise of this form of urban development in the local context has developed as a response to an urban milieu, in which fear has a prevailing role and where the elements of the architecture of fear represent key indicators for its study.